Solitaire Stent Reduced Disability in Stroke Patients in the SWIFT PRIME Trial - Zarifyan, Alla (MD Conference Express, 2015)
The SWIFT PRIME study demonstrated that the Solitaire stent was safe and effective at reducing poststroke disability in patients with acute ischemic stroke. Functional independence (mRS of 0 to 2) at 90 days was achieved in 60.2% of patients in the Solitaire plus IV tPA group vs 35.5% in the IV tPA group (P < .0008).